Enhancing the social issues components in our computing curriculum: Computing for the social good - Goldweber, M.; Davoli, R.; Currie Little, J.; Riedesel, C.; Walker, H.; Cross, G.; Von Konsky, Brian (Association for Computer Machinery (ACM), 2011)
The acceptance and integration of social issues into computing curricula is still a work in progress twenty years after it was first incorporated into the ACM Computing Curricula. Through an international survey of computing instructors, this paper corroborates prior work showing that most institutions include the societal impact of ICT in their programs. However, topics often concentrate on computer history, codes of ethics and intellectual property, while neglecting broader issues of societal impact. This paper explores how these neglected topics can be better developed through a subtle change of focus to the significant role that ICT plays in addressing the needs of the community. Drawing on the survey and a set of implementation cases, the paper provides guidance by means of examples and resources to empower teaching teams to engage students in the application of ICT to bring about positive social outcomes – computing for the social good.